Bahasa Bali dalam Eksistensi Kebudayaan Bali - I Made Suweta (Purwadita : Jurnal Agama dan Budaya, 2019)
Language as a social activity is part of culture. Language is a very important community legacy, its function, position and benefits. Likewise with the Balinese language as a means of communication in Balinese society. Balinese is used as an introduction in Balinese life. In the life of the community, the Balinese language has an important role as a communication tool because the Balinese language is located as a mother tongue. Mother tongue is the first language that is mastered by humans from birth through interactions with fellow members of the language community, such as family and community environment. As a mother tongue, Balinese has a function, namely: a symbol of regional pride and Balinese society, a symbol of Balinese identity, a means of communication within the Balinese family and community, and supporters of Balinese regional literature and the growth of Indonesian language and literature. Based on a brief description of the background of this paper, there are three issues that need to be discussed, namely: what is the nature and elements of Balinese culture?, and how is the relationship between Balinese language and Balinese Culture?